Hereditary transthyretin amyloidosis: baseline characteristics of patients in the NEURO-TTR trial. (3rd July 2018) - Waddington-Cruz, Marcia; Ackermann, Elizabeth J.; Polydefkis, Michael; Heitner, Stephen B.; Dyck, Peter J.; Barroso, Fabio A.; Wang, Annabel K.; Berk, John L.; Dyck, P. James B.; Monia, Brett P.; Hughes, Steven G.; Tai, Li; et al.
Abstract: Background: Hereditary transthyretin (ATTRm) amyloidosis is a rare, progressive and fatal disease with a range of clinical manifestations. Objective: This study comprehensively evaluates disease characteristics in a large, diverse cohort of patients with ATTRm amyloidosis. Methods: Adult patients ( N = 172) with Stage 1 or Stage 2 ATTRm amyloidosis who had polyneuropathy were screened and enrolled across 24 investigative sites and 10 countries in the NEURO-TTR trial (www.clinicaltrials.gov, NCT01737398). Medical and disease history, quality of life, laboratory data, and clinical assessments were analyzed. Results: The NEURO-TTR patient population was diverse in age, disease severity, TTR mutation, and organ involvement. Twenty-seven different TTR mutations were present, with Val30Met being the most common (52%). One third of patients reported early onset disease (before age 50) and the average duration of neuropathy symptoms was 5.3 years. Symptoms affected multiple organs and systems, with nearly 70% of patients exhibiting broad involvement of weakness, sensory loss, and autonomic disturbance. Over 60% of patients had cardiomyopathy, with highest prevalence in the United States (72%) and lowest in South America/Australasia (33%). Cardiac biomarker NT-proBNP correlated with left ventricular wall thickness (p<.001). Quality of life, measured by Norfolk QoL-DN and SF-36 patient-reported questionnaires, was significantly impaired and correlated with disease severity. Conclusions: Baseline data from the NEURO-TTR trial demonstrates ATTRm amyloidosis as a systemic disease with deficits in multiple organs and body systems, leading to decreased quality of life. We report concomitant presentation of polyneuropathy and cardiomyopathy in most patients, and early involvement of multiple body systems.